Electronic spectrum and superconductivity in the t-J model on the honeycomb lattice - Plakida, N.M. (Condensed Matter Physics, 2018)
A microscopic theory of electronic spectrum and superconductivity within the t-J model on the honeycomb lattice is formulated. The Dyson equation for the normal and anomalous Green functions for the two-band model
in terms of the Hubbard operators is derived by applying the Mori-type projection technique. The self-energy
is evaluated in the self-consistent Born approximation for electron scattering on spin and charge fluctuations
induced by the kinematical interaction for the Hubbard operators. Superconducting pairing mediated by the
antiferromagnetic exchange and spin fluctuations is discussed. Сформульована мiкроскопiчна теорiя електронного спектра та надпровiдностi в рамках t-J моделi на
стiльниковiй ґратцi. З допомогою технiки проекцiйних операторiв Морi отримано рiвняння Дайсона для
нормальних i аномальних функцiй Ґрiна для двозонної моделi в термiнах операторiв Хаббарда. Власноенергетична частина розрахована у самоузгодженому борнiвському наближеннi для розсiяння електронiв на спiнових i зарядових флуктуацiях iндукованих кiнематичною взаємодiєю для операторiв Хаббарда.
Обговорюється можливiсть надпровiдного спарювання через антиферомагнiтний обмiн та спiновi флуктуацiї.
Ключовi